2006
DOI: 10.1203/01.pdr.0000191142.56073.f8
|View full text |Cite
|
Sign up to set email alerts
|

Fetal-to-Maternal Transfer of Thyroid Hormone Metabolites in Late Gestation in Sheep

Abstract: 3,3=-diiodothyronine sulfate (T 2 S) derived from T 3 of fetal origin is transferred to the maternal circulation and contributes significantly to the maternal urinary pool. The present study quantitatively assesses the fetal to maternal transfer of T 4 metabolites compared with those of T 3 . Labeled T 4 or T 3 was infused intravenously to four singleton fetuses in utero in each group at gestational age 138 Ϯ 3 d. Maternal and fetal serum and maternal urine samples were collected hourly for 4 h and at 24 h (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In fact, type I deiodinase activity in the liver and kidney of foetus up to the fourth month was lower than that in pre-term foetus or in the newborn (Wu et al, 1992). Low foetal T3 levels are maintained also by sulphation and deiodination (Wu et al, 2006). In the foetus, low T3 levels allow anabolic processes to prevail, despite the high rate of foetal T4 secretion, which resulted eight-fold than maternal one during the last one-third period of gestation (Dussault et al, 1971).…”
Section: Foetal Lifementioning
confidence: 86%
“…In fact, type I deiodinase activity in the liver and kidney of foetus up to the fourth month was lower than that in pre-term foetus or in the newborn (Wu et al, 1992). Low foetal T3 levels are maintained also by sulphation and deiodination (Wu et al, 2006). In the foetus, low T3 levels allow anabolic processes to prevail, despite the high rate of foetal T4 secretion, which resulted eight-fold than maternal one during the last one-third period of gestation (Dussault et al, 1971).…”
Section: Foetal Lifementioning
confidence: 86%
“…In sheep, a precocial species similar to humans, it has been shown that a significant amount of T 3 formed in the fetal circulation is converted to T 2 S and transferred to the maternal compartment for deiodination/excretion (22,23). This process may serve to maintain low circulating T 3 levels in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…The PR for T 4 and T 3 are 46 and Ͻ1.5 g/kg/d, respectively, in the euthyroid third trimester fetus while the PR for rT 3 S, T 4 S, and T 3 S are 12, 10, and 2 g/kg/d, respectively (18,26). The kinetic studies predicted that 3,3=-T 2 S also is a major thyroid hormone metabolite and this was later confirmed qualitatively (25). 3,3=-T 2 S was also found to be the major metabolite in maternal circulation following the fetal infusion of radioactive T 3 (26); a similar immunoreactive product, Compound W, was found peaked at term in pregnant women disappearing 7-10 d after delivery (4,27).…”
Section: Discussionmentioning
confidence: 73%
“…From the high potency of 3=-T 1 in inhibiting sulfoconjugation of 3,3=-T 2 in human SULT1A1 and SULT1A3, 3=-T 1 may be an excellent substrate to be sulfated (24). After the infusion of outer-ringlabeled T 3 in the euthyroid fetus, 3,3=-T 2 S was found to be the predominant metabolite, followed by lesser amounts of 3,3=-T 2 and T 3 S; but no 3=-T 1 or its sulfoconjugate was seen (25). The kinetics of labeled T 3 in Tx ovine fetuses have not been studied with HPLC or other available RIAs specific to sulfated iodothyronines developed recently (7).…”
Section: Discussionmentioning
confidence: 92%